Analyzing the Influence of Tourism Expansion on Regional Spatial Planning and Sustainable Practices: The Mediating Role of Hotel Accommodation in Tomok and Tuktuk Siadong, Samosir Regency, North Sumatra, Indonesia. - Dina Rosari (Socious Journal, 2025)
Tourism development plays a vital role in regional economic growth, especially in culturally and environmentally significant areas such as Tomok and Tuktuk Siadong in Samosir Regency, North Sumatra, Indonesia. This study aims to analyze the influence of tourism expansion on regional spatial planning and sustainable tourism, with a specific focus on the mediating role of hotel accommodation development. Using a quantitative research design, data were collected from [state your actual sample size, e.g., 50] key stakeholders, including local government officials, hotel managers, and community representatives, selected through Slovin’s formula. Structural Equation Modeling with Partial Least Squares (SEM-PLS) was employed to test the hypothesized relationships among variables. The results demonstrate that tourism development significantly influences both regional spatial planning and sustainable tourism outcomes. Crucially, accommodation hotel development is found to partially mediate the relationship between tourism development and regional spatial planning, as well as between tourism development and sustainable tourism. These findings highlight that the growth and practices of the hospitality sector are pivotal in shaping land use, infrastructure demands, and the environmental and socio-cultural dimensions of tourism in the region. The study recommends integrated planning approaches that prioritize sustainable hotel development and enhance stakeholder collaboration to achieve balanced and resilient tourism growth in Tomok and Tuktuk Siadong.